SINDROM TREMOR DAN ATAKSIA TERKAIT FRAGILE X FXTAS RISIKO LAKILAKI PEMBAWA SIFAT SINDROM FRAGILE X - Tri Indah Winarni, Tanjung Ayu Sumekar, Maria Belladona, Farmaditya Eka Putra Mundhofir, Sultana Muh (Neurona Majalah Kedokteran Neuro Sains, 2013)
FRAGILE X ASSOCIATED TREMOR ATAXIA SYNDROME FXTAS IS A PROGRESSIVE NEURODEGENERATIVE DISORDERS IN ELDERLY MALES WHO CARRY FRAGILE X MENTAL RETARDATION 1 FMR1 PREMUTATION ALLELE FRAGILE X SYNDROME CARRIER THE RISK OF FXTAS IS 13 TIMES COMPARED TO NORMAL MALES MAIN CLINICAL FEATURE ARE INTENTION TREMOR AND ATAXIA FXTAS FREQUENTLY MISDIAGNOSIS WITH PARKINSONISM CEREBELLAR TREMOR AND MULTIPLE SYSTEM ATROPHY MSA THE PREVALENCE IS HIGH AND ESTIMATED TO BE 14848 IN GENERAL POPULATION